STRUCTURAL GEOLOGICAL CONTROL ON THE MINERALIZATION ON TABUAN ISLAND,SEMANGKO BAY, SOUTH SUMATERA, INDONESIA - Hananto Kurnio; Ulrich Schwarz Schampera (BULLETIN OF THE MARINE GEOLOGY, 2008)
Mineralization have been discovered on Tabuan Island, Semangko Bay, South Sumatera, Indonesia. Tabuan Island belongs to the Neogene Sunda-Banda magmatic arc system. Tabuan Island is a tectonic horst structure which belongs to the subduction-related, magmatically active Barisan zone along the active continental margin of western Sumatera. Basaltic-andesitic volcanics of the late Oligocene to earliest Miocene Hulusimpang Formation are distributed in a broad zone along and subparallel to the regional Semangko Fault and are hosts for several epithermal-style auriferous deposits. The occurrence of hydrothermal mineralization was first suggested from seismic identification of small intrusive bodies which form elongated northwest-southeast ridges passing through the island. Surface sampling campaigns on the island revealed significant hydrothermal alteration and mineralization with pervasive occurrences of sulphide minerals. Detailed mineralogical and geochemical studies at the Federal Institute for Geoscience and Natural Resources show pronounced disseminations and vein-type mineralization. Mineralization shows moderate enrichments in Au, Ag, Zn, Pb, Cu, As, Sb, Ba, and Mn. The association of subaerial island arc volcanism and subvolcanic intrusive bodies, the regional extensional and strike-slip structural regime, and the occurrence of epithermal-style alteration and mineralization in the same volcanic sequence along the coastal zone of Semangko Bay and on Tabuan Island reveal the great potential of this region for epithermal type Au-Ag and base metal deposits. On Tabuan Island, delineation of structural blocks and fault systems suggests that normal faults and margins of grabens may have acted as fluid channelling structures. Key words: structural geology, mineralization, Tabuan Island, Semangko Bay